Analisis Perubahan Garis Pantai Pada Wilayah Pesisir Kecamatan Amurang Kabupaten Minahasa Selatan Sulawesi Selatan - Kirana, Chandra; Danial, Danial; Asmidar, Asmidar (Program Studi Ilmu Kelautan Fakuktas Ilmu Perikanan dan Kelautan Universitas Muslim Indonesia, 2024)
Chandra, 2023 this study is to determine the extent of coastline changes in the coastal area of Amurang District, South Minahasa Regency and the causes of coastline changes that occur in the Coastal Area of Amurang District, South Minahasa Regency. Changes in coastline are determined by the amount of sediment that goes in and out of each section of the coast. If the incoming sediment is higher than the outgoing, then the beach will experience sedimentation on the contrary, if the incoming sediment is smaller than the outgoing, then the beach will experience erosion. This research was conducted in several stages, namely collecting data and information and analyzing data. Initial image processing consists of image provisioning, image recovery, image cropping, and image sharpening. Field surveys and supporting data collection, as well as advanced image processing which includes classification, supporting data processing, image overlay and interpretation of research results. Changes in the coastline in the coastal area of Amurang District in 5 years average -1.81 Ha, abrasion with a toal of -7.23 Ha and an average accretion of 1.47 Ha with a total of 5.8 Ha, and changes in the coastline in the coastal area of Amurang district are caused by two factors, namely hydro-oceanographic factors that cause abrasion while anthrophogenic factors cause accretion.